Higher subcutaneous adipose tissue radiodensity is associated with increased mortality in patients with cirrhosis - Maryam Ebadi; Abha R. Dunichand-Hoedl; Elora Rider; Norman M. Kneteman; James Shapiro; David Bigam; Khaled Dajani; Vera C. Mazurak; Vickie E. Baracos; Aldo J. Montano-Loza (JHEP Reports, 2022)
Background & Aims: Association between sarcopenia and mortality in cirrhosis is well recognised; however, little is known about the clinical implications of adipose tissue radiodensity, indicative of biological features. This study aimed to determine an association between high subcutaneous adipose tissue (SAT) radiodensity and survival, compare the prevalence of high SAT radiodensity between healthy population and patients with cirrhosis, and identify an association between computed tomography (CT)-measured SAT radiodensity and histological characteristics. Methods: Adult patients with cirrhosis (n = 786) and healthy donors (n = 129) with CT images taken as part of the liver transplant (LT) assessment were included. Abdominal SAT biopsies (1–2 g) were harvested from the incision site at the time of LT from 12 patients with cirrhosis. Results: The majority of patients were male (67%) with a mean model for end-stage liver disease (MELD) score of 15 ± 8. SAT radiodensity above -83 HU in females (sub-distribution hazard ratio [sHR] 1.84, 95% CI 1.20–2.85, p = 0.006) and higher than -74 HU in males (sHR 1.51, 95% CI 1.05–1.18, p = 0.02) was associated with the highest mortality risk after adjusting for confounders in competing risk analysis. The frequency of high SAT radiodensity was 26% for those with cirrhosis, compared with 2% in healthy donors (p <0.001). An inverse correlation was found between SAT radiodensity and the mean cross-sectional area of SAT adipocytes (r = -0.67, p = 0.02). Shrunken, smaller adipocytes with expanded interstitial space were predominant in patients with high SAT radiodensity, whereas larger adipocytes with a thin rim of cytoplasm were observed in patients with low SAT radiodensity (744 ± 400 vs. 1,521 ± 1,035 μm2, p <0.001). Conclusion: High SAT radiodensity frequently presents and is associated with a higher mortality in cirrhosis. SAT morphological rearrangement in patients with high SAT radiodensity might indicate diminished lipid stores and alterations in tissue characteristics. Lay summary: Poor quality of subcutaneous adipose tissue (fat under the skin) is associated with higher mortality in patients with end-stage liver disease. Fat cells are smaller in patients with poor adipose tissue quality.